2023
DOI: 10.1200/jco.2023.41.4_suppl.607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and mutational profiles of microsatellite instability (MSI-H) in intrahepatic cholangiocarcinoma (iCCA).

Abstract: 607 Background: Microsatellite instability (MSI-H) and increased tumor mutation burden (TMB) have been associated with clinical benefit from immunotherapy. A small subset of patients with intrahepatic cholangiocarcinoma (iCCA) have microsatellite instability (MSI-H). Understanding their clinical outcomes and genomic landscape has been limited. These patients may derive clinical benefit from immunotherapy compared to chemotherapy. Methods: 7565 cases of iCCA underwent comprehensive genomic profiling of 324 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In intrahepatic CCA, rates were similar at 2.5% MSI-H (n=5/198) and 3.5% TMB-H (n=7/198) ( 21 ). Rates of MSI-H in biliary tract cancers in other studies have been similar in the 1–3% range ( 22 , 23 ).…”
supporting
confidence: 65%
“…In intrahepatic CCA, rates were similar at 2.5% MSI-H (n=5/198) and 3.5% TMB-H (n=7/198) ( 21 ). Rates of MSI-H in biliary tract cancers in other studies have been similar in the 1–3% range ( 22 , 23 ).…”
supporting
confidence: 65%
“…Nearly 8.7% of the patients belonged to the TMB-H group in the MSS group, while all (100%) of the MSI-H patients belonged to the TMB-H group, which can also be recommended to use the PD-1 inhibitor pembrolizumab (level I). Similarly, Eluri et al also observed that MSI-H cases had lower frequencies of previously identified, actionable ICC drivers, such as FGFR2 fusions (0% vs. 9%, p = NS), IDH1 (3.7% vs. 14.5%, p < 0.0001), and IDH2 (0% vs. 4.1%, p = 0.007) [ 50 ]. Different gene alterations and co-altered patterns may partly explain the low prevalence of PAT for other precision medicines except for ICI in the MSI-H CCA group [ 51 ].…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Eluri et al reported that the frequency of MSI-H in 7565 ICC cases was 1.8%, and the median TMB of MSI-H patients was 21.7 muts/Mb. Meanwhile, the study also showed that genomic alterations in TP53 (59.9%), PRBM1 (37.2%), ARID1A (13.9%), and APC (13.9%) were enriched in patients with MSI-H [ 50 ]. In another study, RNF43 and KMT2D mutations frequently occurred in CCA patients with MSI-H and TMB-H status [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation